(untitled) (PYC Nepal Journal of Management, 2024)
SMEs in Nepal also have constrained access to finance, due to exorbitant interest rates, cumbersome procedures, dearth of knowledge, and inadequate institutional capacity. Analyzing SME business taxpayers’ perceptions of Nepalese tax system is the study’s primary goal. For this, descriptive research designed was used. The primary data comprised 340 (94.44%) valid respondents through questionnaire from Tripureshwor, Kathmandu with purposive judgmental sampling whereas secondary sources were research scholar’s articles and IRD annual reports. Jamovi was used to analyze the factor, ANOVA, regression and reliability testing. The findings indicate that the four independent variables behavior tax obligation, tax system, tax policies and government activities, and tax compliance account for 96.3% of respondents’ perception which is also significantly asserted by regression result. Government should give the incentives, for formalizing the decision to comply with effective tax regulations.